Development of Game-Based Mobile Learning Application: Run for Health - ER, JIA WEI; BINTI CHE DALIM, CHE SAMIHAH (Applied Information Technology And Computer Science, 2024)
Understanding nutrition is vital for informed dietary decisions. However, the current approach to nutrition education faces challenges like inconsistency, misinformation, and undue emphasis on personal responsibility, adversely affecting individuals and society. To address these issues, this study developed "Run for Health," an interactive app for children aged 7 to 12 to learn about nutrition during their leisure time. Nutritional apps are key to promoting healthier lifestyles, but they face challenges in user interface and experience design. This project aimed to fill a gap in the 2D platformer genre on the Google Play Store by developing the game on Android using Unity. The app's functionality and user acceptance were tested on the target audience at Sekolah Kebangsaan Pintas Raya. The results indicate that "Run for Health" was well-received by its target users, achieving the project’s objectives successfully.